(untitled) (Revista de Ciências Agroveterinárias, 2025)
The search for healthy eating has sparked consumer interest not only in fast foods such as hamburgers, but also in more nutritious foods with fewer synthetic additives. In this sense, this study investigated the effect of applying lemon peel essential oil as a natural preservative in beef burgers on physical-chemical parameters, cooking characteristics, and microbiological quality. The essential oil was extracted from Tahiti lime peels and its chemical composition was determined, as well as yield (%) and density (g/L). Three hamburger formulations were produced: HC (without preservatives), HS (with added synthetic preservatives), and HE (with added essential oil). Physical-chemical analyses were performed, including the determination of moisture, lipids, proteins, and ash. In addition, the cooking characteristics of the hamburgers were also verified. The pH and color were monitored during storage at refrigeration temperature (5 °C) for five days and freezing (-18 °C) for 10 and 20 days. To assess microbiological quality, analyses were performed to identify Salmonella sp., quantify Escherichia coli, and identify mesophilic aerobic bacteria. The essential oil showed a satisfactory yield (1.74%) and characteristic density (0.881 g/L), containing d-limonene (45.67%) as the major compound. The addition of oil did not alter most of the physical-chemical parameters of the hamburger, except for a slight reduction in protein content. The pH (<5.8) and color remained stable in the HE formulation and showed no significant differences with the addition of essential oil compared to the control formulation (HC). The essential oil also did not affect the cooking characteristics. Microbiological analyses showed no contamination by pathogenic bacteria according to current legislation. Therefore, the addition of lemon essential oil as a natural preservative proved to be viable in beef burgers, maintaining the physicochemical characteristics, cooking characteristics, and microbiological quality of the beef burger.